Role of In-store Atmospherics and Impulse Buying Tendency on Post Purchase Regret in Kathmandu Valley - Pokharel, Richa (Nepalese Journal of Management, 2024)
This study examines the role of in-store atmospherics and impulse buying tendency on post purchase regret in Kathmandu Valley. The dependent variable of the study are impulse buying tendency and post purchase regret. Similarly, the selected independent variables are store ambient factor, store design factor, visual merchandising, sales person and sales promotion. The primary source of data is used to assess the opinions of the respondents regarding store ambient factor, store design factor, visual merchandising, sales person, sales promotion on impulse buying tendency and post purchase regret. The study is based on primary data of 110 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance in-store atmospherics and impulse buying tendency on post purchase regret in Kathmandu Valley. The study showed that store ambient factor has positive impact on impulse buying tendency. It implies that more stimulating or conducive store ambient factor through strategic placement of products, appealing displays, or background music leads to impulse buying tendency. Similarly, store design factor has positive impact on impulse buying tendency. It indicates that better design of the store stimulates the impulse buying tendency of the customers. Likewise, visual merchandising has positive impact on impulse buying tendency. It shows that use of effective, consistent and high-quality visual merchandising leads to impulse buying tendency of the customers. In addition, salespersons have positive impact on impulse buying tendencies. It implies that knowledgeable and trustworthy salespersons with good product knowledge and expertise lead to impulse buying tendency of the customers. Furthermore, sales promotions have positive impact on impulse buying tendency and post purchase regret. It implies that increase in sales promotions such as discounted prices or with additional incentives such as free gifts, coupons, or buy-one-get-one offers, leads to increase in consumer impulse buying tendency. Moreover, impulse buying tendency has positive impact on post purchase regret. It implies that impulse purchases driven by emotions, urges, or situational factors rather than rational decision-making leads to increase in post purchase regret.